Pengukuran Kreativitas melalui Teknik Non Tes serta Contoh Teknik Non Tes dalam Pengukuran Kreativitas (Studi Pendidikan Anak Usia Dini) - Siti Maghfhirah; Khamim Zarkasih Putro (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
Realized children's creativity is well characterized by being able to solve the problems at hand, be able to do tasks with enthusiasm, curiosity, can play their imagination when playing roles, etc. Children's creativity must be stimulated from an early age so that children are ready to face all challenges in the future, of course, with age-appropriate techniques and methods of delivery. Naturally, the curiosity and desire to learn something already exists in the child who has been gifted by God. So naturally children also have the ability to learn creativity through something in their own way. A child, especially at the age of a baby, when doing some creative activities will try to glance and then reach for objects that interest him. Then he will put the object in his mouth. In this way babies recognize and distinguish objects. Some creative activities include how to make dolls from socks and so on. After the child has done the activity, the teacher should give and show an attitude assessment to appreciate the child's work. Through an attitude of appreciating the child's work in any form, including the principle character. Children really need stimulus, praise and feel appreciated. Without this attitude, it is impossible for children to be willing to express themselves freely and independently in completing their tasks. The teacher must also give a fair assessment of each child's work, all assessments are carried out according to the child's creative abilities.